CORRELATION OF URIC ACID AND TRIGLYCERIDE LEVELS IN CHD PATIENTS AT BUDHI ASIH HOSPITAL, EAST JAKARTA - Heru Setiawan; Eka Puji Lestari (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
NCD is the number one cause of death is cardiovascular disease. Hyperuricemia is a risk factor for CHD that causes endothelial dysfunction, accelerates the deterioration of the heart muscle, resulting in an acute phase of heart failure. Hypertriglyceridemia is also a risk factor for CHD. In several research studies on CHD, there are still many that are not clear in revealing the correlation between uric acid and triglycerides in CHD patients. Facts in the field show that more than 50% of patients who enter the special inpatient room for heart disease at Budhi Asih General Hospital are examined for lipid profiles with uric acid simultaneously as the first examination. This study aims to determine the correlation between uric acid and triglyceride levels in CHD patients at Budhi Asih General Hospital. This study uses a correlative analytic design. Secondary data were taken from medical records as well as data from the results of uric acid and triglyceride examinations in the laboratory which were processed with SPSS statistical test equipment. The research subjects were inpatients specifically for heart disease at Budhi Asih Hospital for the period January 2022-May 2022 who were examined simultaneously for uric acid and triglycerides. Descriptively the mean age of patients with CHD is 56 years. The mean uric acid level in CHD patients was 8.06 mg/dL, the mean triglyceride level was 198.2 mg/dL. CHD patients with high levels of uric acid and triglycerides are more common in men. Data analysis using Spearman's correlation test, from 51 research samples obtained p value 0.000 <0.05, which means there is a correlation between uric acid and triglyceride levels in CHD patients with a correlation coefficient value of 0.681. The conclusion of this study is that there is a correlation between uric acid and triglycerides in patients with CHD in Budhi Asih Hospital. The direction of the positive correlation, the higher the uric acid level, the higher the triglyceride level. Keywords: CHD, Uric Acid, Triglycerides, Correlation